GAMBARAN PERILAKU ORAL HYGIENE, SKOR PLAK dan SKOR GINGIVA PADA PENDERITA DIABETES MELITUS (STUDI DI RSUD TUGUREJO SEMARANG) - Christanto Ismu Priyo Boka Wayeni; Henry Setyawan Susanto; Arie Wuryanto (Jurnal Kesehatan Masyarakat (Undip), 2019)
Background : Diabetes mellitus is a degenerative disease that is known to cause an increased risk of dental and oral health problems, especially plaque buildup and gingival disorders. DM prevalence in Indonesia ranges from 6.9% of the population and dental and oral health problems in Indonesia reach 25.9%.Objective : This study aimes to describe the behavior of oral hygiene, plaque scores and gingival scores in people with diabetes mellitus..Method : This research used 30 respondents based on the results of the Slovin formula, makes diabetic patients were examining internal medicine poly as samples by convenience sampling method. The research data analysis was univariate and bivariate analysis. This type of research is an observational descriptive research with a cross sectional study design.Results : On average, patients with diabetes mellitus who were used as respondents in this study had poor oral hygiene behavior (50%) with a low level of knowledge of oral hygiene (63.3%). On average, diabetic patients have an alarming plaque index status (66.7%) and a gingival index of (43.3%) have poor gingival status.Conclusion : The level of diabetics is still not aware of maintaining dental and oral hygiene due to the lack of knowledge about this. Based on this research, it is expected that there will be more socialization and awareness to diligently check dental and oral health, especially in patients with diabetes mellitus.